Impact resistance of oil palm shells concrete reinforced with polypropylene fibre - Yahaghi J.; Muda Z.C.; Beddu S.B. (Elsevier Ltd, 2023)
Concrete mixtures; Cracks; Drops; Ductility; Fibers; Impact resistance; Machinery; Palm oil; Polypropylenes; Reinforced plastics; Reinforcement; Concrete cutting; Concrete reinforced; Crack resistance; Drop weight impact; Environmental influences; Low velocities; Oil palm; Polypropylene fibres; Light weight concrete